Partitioning evapotranspiration – Testing the Craig and Gordon model with field measurements of oxygen isotope ratios of evaporative fluxes - Dubbert, Maren; Cuntz, Matthias; Piayda, Arndt; Máguas, Cristina; Werner, Christiane (Journal of Hydrology, 2013)
su mmary Stable oxygen isotopes of water provide a valuable tracer for water movements within ecosystems and are used to estimate the contribution of transpiration to total ecosystem evapotranspiration (ft). We tested the Craig and Gordon equation against continuous field measurements of isotopic composition of evaporation and assessed the impact for partitioning evapotranspiration. Therefore, evaporation (E) and its isotopic signature (d18OE) on bare soil plots, as well as evapotranspiration (ET) and its correspond- ing isotopic composition of (d18OET) of an herbaceous layer was measured with a cavity ring-down spec- trometer connected to a soil chamber on a field site in central Portugal. We quantified the variation in d18OE arising from uncertainties in the determination of environmental input variables to the Craig and Gordon equation: the isotope signature (d18Oe) and the temperature at the evaporating site (Te), and the kinetic fractionation factor (ak). We could hence quantify ft based on measured d18OET, modeled d18OE from observed soil water isotopic composition at the evaporating site (d18Oe), and modeled d18O of transpiration (d18OT) from observed total soil water isotopic composition. Our results demonstrate that predicting d18OE using the Craig and Gordon equation leads to good agree- ment with measured d18OE given that the temperature and 18O isotope profiles of the soil are thoroughly characterized. However, modeled d18OE is highly sensitive to changes in Te and d18Oe as well as ak. This markedly affected the partition results of transpiration and evaporation from the total ET flux: The frac- tion of transpiration (ft) varied strongly using different formulations for ak and assuming steady or non- steady state transpiration. These findings provide a first comparison of laser-based and modeled isotopic compositions of evaporation based on the Craig and Gordon equation under field conditions. This is of special interest for studies using stable isotopes to separate soil evaporation and plant transpiration fluxes and highlights the need for a thorough characterization of the micrometeorological and isotopic constitution of the upper soil layer to locate the evaporating front with a resolution of a few cm soil depths. We also call on a better characterization of the kinetic fractionation factor of soil evaporation.
Keywords: Craig and Gordon; evaporation; Evapotranspiration; Kinetic fractionation; Laser spectroscopy; Stable oxygen isotopes

A step towards the use of biomonitors as estimators of atmospheric PAHs for regulatory purposes. - Augusto, Sofia; Pereira, Maria J.; Máguas, Cristina; Branquinho, Cristina (Chemosphere, 2013)
One of the main drawbacks of using lichens to monitor atmospheric PAHs has been reported as the inexistence of studies aiming to translate PAH values in lichens into the atmospheric equivalents ones, in order to use this information for regulatory purposes. In this work, PAH concentrations in lichens were compared with PAH concentrations measured in a conventional active sampler in an outdoor environment for a 9-month span. Significant positive correlations between HMW-PAHs, Σ16 EPA-PAHs, and BaP equivalent concentrations in lichens and those in air (TSP) were found. Concentrations of Σ16 EPA-PAHs in lichens and air showed a seasonal variation, with highest values during winter and lowest values during summer. Meteorological variables - temperature, atmospheric pressure, relative humidity, and wind speed - showed to significantly influence PAH concentrations in both lichens and air. Based on the significant linear correlations, equations for translating PAH concentrations measured in lichens into equivalent ones for air were proposed for the first time, allowing a broader use of lichens' information regarding PAHs in monitoring schemes and decision-making.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23668962
Keywords: Air; BaP; Biomonitors; Environment; Human health; PAHs

Using lichen functional diversity to assess the effects of atmospheric ammonia in Mediterranean woodlands - Pinho, Pedro; Dias, Teresa; Cruz, Cristina; Sim Tang, Y; Sutton, Mark A; Martins-Loução, Maria-Amélia; Máguas, Cristina; Branquinho, Cristina (Journal of Applied Ecology, 2011)
1. Atmospheric ammonia (NH3) is one of the main drivers for ecosystem changes world-wide, including biodiversity loss. Modelling its deposition to evaluate its impact on ecosystems has been the focus of many studies. For that, universal indicators are needed to determine and compare the early effects of NH3 across ecosystems. 2. We evaluate the effects of atmospheric NH3 in ecosystems using lichens, which are one of the most sensitive communities at the ecosystem level. Rather than measuring total diversity, we use a functional diversity approach because this is potentially a more universal tool. 3. We evaluated the spatial and temporal patterns of atmospheric NH3 concentrations ([NH3]atm) emitted from a point-source over a 1-year period in a cork oak Mediterranean woodland. We observed a temporal pattern of [NH3]atm, with maximum concentrations during autumn. 4. The distribution of lichen species was c. 90% explained by [NH3]atm. The tolerance of lichen species to atmospheric NH3, based on expert knowledge from literature, was tested for the first time against direct measurements of atmospheric NH3. Most species were well classified, with the exception of Lecanora albella and Chrysothrix candelaris, which were more tolerant than expected. Our updated lichen classification can be used to establish lichen functional groups that respond to atmospheric NH3, and these can be used in other Mediterranean countries. 5. Increasing [NH3]atm led to a complete replacement of oligotrophic by nitrophytic species within 65 m of the NH3 source. The geostatistical analysis of functional diversity variables yielded a spatial model with low non-spatial variance, indicating that these variables can cope robustly with high spatial variation in NH3. 6. Synthesis and applications. Our results support the use of functional diversity variables, such as a lichen diversity value, as accurate and robust indicators of the effects of atmospheric NH3 on ecosystems. The spatial modelling of these indicators can provide information with high spatial resolution about the effects of atmospheric NH3 around point- and diffuse sources. As this methodology is based on functional groups, it can be applied to monitor both the impact of atmospheric NH3 and the success of mitigation strategies.
Keywords: Agriculture; atmospheric NH3; biodiversity loss; Cattle; Ecological indicators; Global change; spatial analysis

Disentangling drought-induced variation in ecosystem and soil respiration using stable carbon isotopes. - Unger, Stephan; Máguas, Cristina; Pereira, João S; Aires, Luis M; David, Teresa S; Werner, Christiane (Oecologia, 2010)
Combining C flux measurements with information on their isotopic composition can yield a process-based understanding of ecosystem C dynamics. We studied the variations in both respiratory fluxes and their stable C isotopic compositions (delta(13)C) for all major components (trees, understory, roots and soil microorganisms) in a Mediterranean oak savannah during a period with increasing drought. We found large drought-induced and diurnal dynamics in isotopic compositions of soil, root and foliage respiration (delta(13)C(res)). Soil respiration was the largest contributor to ecosystem respiration (R (eco)), exhibiting a depleted isotopic signature and no marked variations with increasing drought, similar to ecosystem respired delta(13)CO(2), providing evidence for a stable C-source and minor influence of recent photosynthate from plants. Short-term and diurnal variations in delta(13)C(res) of foliage and roots (up to 8 and 4 per thousand, respectively) were in agreement with: (1) recent hypotheses on post-photosynthetic fractionation processes, (2) substrate changes with decreasing assimilation rates in combination with increased respiratory demand, and (3) decreased phosphoenolpyruvate carboxylase activity in drying roots, while altered photosynthetic discrimination was not responsible for the observed changes in delta(13)C(res). We applied a flux-based and an isotopic flux-based mass balance, yielding good agreement at the soil scale, while the isotopic mass balance at the ecosystem scale was not conserved. This was mainly caused by uncertainties in Keeling plot intercepts at the ecosystem scale due to small CO(2) gradients and large differences in delta(13)C(res) of the different component fluxes. Overall, stable isotopes provided valuable new insights into the drought-related variations of ecosystem C dynamics, encouraging future studies but also highlighting the need of improved methodology to disentangle short-term dynamics of isotopic composition of R (eco).
Keywords: Drought; Ecosystem respired carbon dioxide stable isotopic; Keeling plots; Mediterranean ecosystem; Respired carbon dioxide

The influence of precipitation pulses on soil respiration – Assessing the “Birch effect” by stable carbon isotopes - Unger, Stephan; Máguas, Cristina; Pereira, João S.; David, Teresa S.; Werner, Christiane (Soil Biology and Biochemistry, 2010)
Sudden pulse-like events of rapidly increasing CO2-efﬂux occur in soils under seasonally dry climates in response to rewetting after drought. These occurrences, termed “Birch effect”, can have a marked inﬂuence on the ecosystem carbon balance. Current hypotheses indicate that the “Birch” pulse is caused by rapidly increased respiration and mineralization rates in response to changing moisture conditions but the underlying mechanisms are still unclear. Here, we present data from an experimental ﬁeld study using straight-forward stable isotope methodology to gather new insights into the processes induced by rewetting of dried soils and evaluate current hypotheses for the “Birch“-CO2-pulse. Two irrigation experiments were conducted on bare soil, root-free soil and intact vegetation during May and August 2005 in a semi-arid Mediterranean holm oak forest in southern Portugal. We continuously monitored CO2-ﬂuxes along with their isotopic compositions before, during and after the irrigation. d 13 C signatures of the ﬁrst CO2-efﬂux burst, occurring immediately after rewetting, ﬁt the hypothesis that the “Birch” pulse is caused by the rapid mineralization of either dead microbial biomass or osmoregulatory substances released by soil microorganisms in response to hypo-osmotic stress in order to avoid cell lyses. The response of soil CO2-efﬂux to rewetting was smaller under mild (May) than under severe drought (August) and isotopic compositions indicated a larger contribution of anaplerotic carbon uptake with increasing soil desiccation. Both length and severity of drought periods probably play a key role for the microbial response to the rewetting of soils and thus for ecosystem carbon sequestration.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Birch effect; d13C; Irrigation experiment; Mediterranean woodland; Soil respiration; Stable isotopes